2019
DOI: 10.5455/javar.2019.f332
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of aflatoxin M1 residues in market milk in Aswan Province, Egypt and effect of probiotics on its residues concentration

Abstract: Objective: The objectives of our study were to determine the presence of Aflatoxin M1 (AFM1) in market milk in Aswan province, Egypt and studying the effect of addition of some strains of probiotics microorganisms on AFM1 level in milk. Materials and Methods: Between July and October 2018, 90 market milk samples (15 Ultra Heat Treated (UHT), 75 raw) were collected from different dairy shops in Aswan City, Egypt to be examined for AFM1 presence by rapid strip test and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These data were near to some extent to the obtained results where the obtained mean concentration of AFM1 in winter samples was 480 ng/L, and that in summer samples was 230 ng/L. In Aswan, Zakaria et al (2019) documented that 49% of raw milk samples were positive for AFM1 residues. All 37 positive milk samples showed that the level of AFM1 ranged between 0.053 and 0.207 with a mean ±SE of 0.1003 ± 0.008 ppb, these results were lower than ours.…”
Section: Discussionsupporting
confidence: 83%
“…These data were near to some extent to the obtained results where the obtained mean concentration of AFM1 in winter samples was 480 ng/L, and that in summer samples was 230 ng/L. In Aswan, Zakaria et al (2019) documented that 49% of raw milk samples were positive for AFM1 residues. All 37 positive milk samples showed that the level of AFM1 ranged between 0.053 and 0.207 with a mean ±SE of 0.1003 ± 0.008 ppb, these results were lower than ours.…”
Section: Discussionsupporting
confidence: 83%
“…When yogurt is produced from AFM 1 -contaminated milk, the toxin with potential carcinogenic properties can still be present during the process of fermentation, even though the developing acidity can reduce AFM 1 levels through several mechanisms involving peptidoglycans, cell-wall polysaccharides and proteins (59) . Nevertheless, a previous study showed that pasteurisation was not effective in reducing the formation of this toxin (60,62) .…”
Section: Discussionmentioning
confidence: 91%
“…There are several safety risks associated with milk that originate from exposure of milk to chemicals, microbial contamination, illegal additives, aflatoxins [ 7 – 9 ], veterinary drugs [ 10 , 11 ] and heavy metals [ 12 ]. Heavy metals are one of the most dangerous environmental pollutants that contaminate the milk creating significant risk to consumers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%